Biohybrid Vaccines for Improved Treatment of Aggressive Melanoma with Checkpoint Inhibitor - Fontana F; Fusciello M; Groeneveldt C; Capasso C; Chiaro J; Feola S; Liu ZH; Mäkilä EM; Salonen JJ; Hirvonen JT; Cerullo V; Santos HA (AMER CHEMICAL SOC, 2022)
Recent approaches in the treatment of cancer focus on involving the immune system to control the tumor growth. The administration of immunotherapies, like checkpoint inhibitors, has shown impressive results in the long term survival of patients. Cancer vaccines are being investigated as further tools to prime tumor-specific immunity. Biomaterials show potential as adjuvants in the formulation of vaccines, and biomimetic elements derived from the membrane of tumor cells may widen the range of antigens contained in the vaccine. Here, we show how mice presenting an aggressive melanoma tumor model treated twice with the complete nanovaccine formulation showed control on the tumor progression, while in a less aggressive model, the animals showed remission and control on the tumor progression, with a modification in the immunological profile of the tumor microenvironment. We also prove that co-administration of the nanovaccine together with a checkpoint inhibitor increases the efficacy of the treatment (87.5% of the animals responding, with 2 remissions) compared to the checkpoint inhibitor alone in the B16.0VA model. Our platform thereby shows potential applications as a cancer nanovaccine in combination with the standard clinical care treatment for melanoma cancers.